2014
DOI: 10.1016/j.apsusc.2014.06.197
|View full text |Cite
|
Sign up to set email alerts
|

Dominantly epitaxial growth of graphene on Ni (1 1 1) substrate

Abstract: Graphene was grown on a Ni (111) thin layer, used as a substrate. The Ni layer itself was grown on single crystal sapphire (0001). Carbon was deposited by chemical vapor deposition using a mixture of methane, argon and hydrogen at atmospheric pressure implementing a constant gas flow (4.8-5 l/min) varying both the gas composition and the deposition temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Escape of carbon atoms on the surface occurs through the favourable domain boundaries, which in the places of entrance to the surface form the nucleation sites for multilayer graphene growth along the Ni surface [25]. It should be noted that some grain boundaries act as a fast diffusion path or enhanced local carbon sources in comparison with diffusion through the bulk Ni.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Escape of carbon atoms on the surface occurs through the favourable domain boundaries, which in the places of entrance to the surface form the nucleation sites for multilayer graphene growth along the Ni surface [25]. It should be noted that some grain boundaries act as a fast diffusion path or enhanced local carbon sources in comparison with diffusion through the bulk Ni.…”
Section: Resultsmentioning
confidence: 99%
“…For limiting the heterogeneity of graphene coating by CVD, several steps were taken to improve the structure of the deposited polycrystalline nickel substrate -for the approximation to the Ni single crystal structure [25]. The resulting coating was epitaxially grown graphene with areas up to 1 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported an increase in texturing in the (1 1 1) orientation by heating the substrate during thin film deposition [34]. To study the effects of substrate heating on texture, two 100 nm thick Ni films (Ni9 and Ni10) were grown at a substrate temperature of 450 °C.…”
Section: Substrate Heatingmentioning
confidence: 99%
“…Sapphire crystals are widely used as substrates to grow metal films due to their high thermal and chemical stabilities, necessary for withstanding the harsh conditions of the CVD process required for the synthesis of high-quality graphene. [27][28][29][30] Single crystal iridium(111) films can be deposited by pulsed laser deposition (PLD) 24 and metal-organic CVD 31 on (0001) sapphire single crystals. Deposition of epitaxial iridium films on other orientations of sapphire was also reported by using the method of metal-organic CVD and an epitaxial relationship between different orientations a) Electronic mail: arti.pandey@desy.de b)…”
mentioning
confidence: 99%